Small is Necessary Shared Living on a Shared Planet - Nelson, Anitra (Pluto Press, 2018)
Does small mean less? Not necessarily. In an era of housing crises, environmental unsustainability and social fragmentation, the need for more sociable, affordable and sustainable housing is vital. The answer? Shared living - from joint households to land-sharing, cohousing and ecovillages.Using successful examples from a range of countries, Anitra Nelson shows how 'eco-collaborative housing' - resident-driven low impact living with shared facilities and activities - can address the great social, economic and sustainability challenges that householders and capitalist societies face today. Sharing living spaces and facilities results in householders having more amenities and opportunities for neighbourly interaction.Small is Necessary places contemporary models of 'alternative' housing and living at centre stage arguing that they are outward-looking, culturally rich, with low ecological footprints and offer governance techniques for a more equitable and sustainable future.